Investigating gaps in the application of financial management systems by schools receiving section 21 funding : case study for Mthatha education district schools - Eastern Cape province - Makrwede, Fundiswa (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPA)--Stellenbosch University, 2012.